2020
DOI: 10.3389/fpsyt.2020.00768
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Psychosocial Interventions Targeting Hazardous and Harmful Alcohol Use and Alcohol-Related Symptoms in Low- and Middle-Income Countries: A Systematic Review

Abstract: Background: In low-and middle-income countries (LMIC), the mismatch between the number of individuals needing and those receiving treatment for alcohol use disorders (AUD) is substantial. In order to provide suggestions for the scaling up of effective service provision we systematically reviewed the current evidence on the effectiveness of AUDfocused psychosocial interventions in LMIC. Methods: We used a systematic review methodology following the PRISMA guidelines. Twelve electronic databases listing publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 135 publications
(404 reference statements)
0
10
0
Order By: Relevance
“…Problem-solving helps individuals manage stressful situations and develop alternative coping strategies integral to relapse prevention (Demirbas et al, 2012), with problem-solving therapy being a widely used evidence-based SUD treatment (Preusse et al, 2020). Problem-solving and social support ( unspecified ) were also among the most frequently used promising BCTs identified by Brown et al (2019) for the prevention of postpartum smoking relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Problem-solving helps individuals manage stressful situations and develop alternative coping strategies integral to relapse prevention (Demirbas et al, 2012), with problem-solving therapy being a widely used evidence-based SUD treatment (Preusse et al, 2020). Problem-solving and social support ( unspecified ) were also among the most frequently used promising BCTs identified by Brown et al (2019) for the prevention of postpartum smoking relapse.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of these treatments on concurrent AUD has not been evaluated. Similarly, while there is evidence that AUD treatments such as CBT, motivational interviewing and structured brief interventions are effective in reducing alcohol use and alcohol-related harm in LMIC settings (Preusse, Neuner and Ertl, 2020;Ghosh et al, 2022; https://doi.org/10.1017/gmh.2022.63 Published online by Cambridge University Press Staton et al, 2022), effects on concurrent PTSD have seldom been reported. It is also unclear whether PTSD+AUD acts as a moderator on treatment outcomes.…”
Section: Treatment Of Ptsd+aud In Lmicsmentioning
confidence: 99%
“…Furthermore, the WHO broadened the view from a European to a global level when formulating a 'Global strategy to reduce the harmful use of alcohol' in 2010, now including low-and middle-income countries for the first time [6,8]. This in turn resulted in further research on alcohol-use prevention as, for example, shown in the review of Preusse et al [14] who specifically reviewed programs to prevent harmful alcohol-use in low-and middle-income countries. They were able to include 21 studies of which the vast majority (k = 18) were published after 2010.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn resulted in further research on alcohol‐use prevention as, for example, shown in the review of Preusse et al . [14] who specifically reviewed programs to prevent harmful alcohol‐use in low‐ and middle‐income countries. They were able to include 21 studies of which the vast majority ( k = 18) were published after 2010.…”
Section: Introductionmentioning
confidence: 99%